Qualitative Methods in Health Policy and Systems Research: A Framework for Study Planning. (October 2020) - Fisher, Michael P.; Hamer, Mika K.
Qualitative methodologies and methods are commonly used in health policy and systems research but have not been extensively characterized. We describe how qualitative approaches are used within the field and present a framework to aid researchers in study planning. To achieve these aims, we conducted a scoping literature review of 1 year of selected health policy and systems research and then coded publications based on their primary analytical foci. Four core themes emerged: policy or program content, an analysis of the substance of policies or program documents; policy or program environment, a study of the landscape of policies or programs; policy or program implementation, a study of the planned or actual execution of a policy or program; and organization or system operations, a study of the structure or function of health organizations or systems. We provide guidance on utilizing the framework and adhering to qualitative best practices during the process.